Capital Market Reaction of Trade Wars (Event Study on the South Korean and Indonesia Stock Exchanges) - Satryo, Andre Ageng; Wijayanto, Andhi (Management Analysis Journal, 2019)
The purpose of this research is to find out whether there are differences in average abnormal returns, average trading volume activity and average security return variability between before and after the Chinese trade war events by the United States in Indonesia and South Korea. The purposive sampling method was used to determine the sample size of 2 countries, namely Indonesia and South Korea. The study period was limited to t-7 before the event and t + 7 after the event. Data analysis method used to answer hypotheses used data normality and Wilcoxon Sign Rank Test difference test. The results showed that all research variables were not normally distributed. Therefore, hypothesis testing is performed using the Wilcoxon Sign Test. The results obtained from the Wilcoxon Sign Test are that there is no significant difference in average abnormal return and average security return varibality both before and after the Chinese Trade War Event by the United States in Indonesia. While there are significant differences in average trading volume activity before and after the Tiongkok-United States Trade War events in Indonesia and South Korea. The conclusion from the research shows that H1 and H3 are rejected, which means there is no difference in average abnormal return and average security return varibality before and after trade war events. H2 was accepted which showed that there were differences in average trading volume activity before and after the Chinese trade war by the United States. For further research, it is expected to be able to add literature and references by taking into account the limitations in this study and using other event studies to become research material.